Interfaith Dialogue in the Context of Globalization: The Role of Religion in International Diplomacy - Johannis Siahaya; Achmad Siddiq; Ilham Tri Murdo; Muhammad Nafi; Syahrir Ibnu (GoAcademica Research & Publishing, 2023)
This article examines the significant role of interfaith dialogue in facilitating cooperation between countries, promoting peace, and influencing foreign policy. This research uses qualitative methods with data collected through primary and secondary data. Primary data was obtained through in-depth interviews with diplomats, religious leaders, and community figures involved in the interfaith dialogue process in the context of international diplomacy. Secondary data is collected from sources such as diplomatic reports, international agreements, and relevant academic publications. Through concrete examples such as peace agreements in various conflicts, interfaith dialogue has proven effective in reducing religious tensions and supporting reconciliation between communities. However, challenges such as religious conflict, the politicization of religion, and the influence of globalization are also present in efforts to facilitate this dialogue. Therefore, this article underlines the importance of carrying out interfaith dialogue carefully, based on the principles of neutrality, respect for beliefs, and mutual understanding, to achieve the goals of international diplomacy and global peace in this era of globalization.